The role of Shenqi Fuzheng injection as adjuvant therapy for breast cancer: an overview of systematic reviews and meta-analyses - Jing Xu; Xiao Li; Liyuan Lv; Qing Dong; Xiaofeng Du; Guangda Li; Li Hou (BMC, 2024)
Abstract Background Breast cancer (BC) is the most frequent malignancy in the world. Chemotherapy (CT) is a common treatment for BC but is accompanied by toxicity and side effects. Shenqi Fuzheng Injection (SFI) is an adjuvant therapy with promising results in improving efficacy and reducing toxicity in clinical studies. This overview of systematic reviews and meta-analysis (SRs/MAs) aimed to summarize the benefits and evaluate the quality of evidence supporting SFI adjuvant as CT for BC. Methods A systematic search for SRs/MAs of randomized controlled trials (RCTs) on SFI treatment for BC was performed by searching PubMed, Web of Science, EMbase, Cochrane Library, CNKI, Wanfang, VIP, and SinoMed databases from inception to October 1, 2022. The quality of SRs/MAs was evaluated using AMSTAR-2, PRISMA 2020, ROBIS, and GRADE by two reviewers. The corrected covered area (CCA) was used to quantify the degree of duplication of the original SRs/MAs. Finally, quantitative analysis of RCTs was conducted using RevMan 5.4 software. This study was registered with PROSPERO, CRD42022377290. Results Six SRs/MAs including 61 RCTs with 5593 patients were included in this study. Studies were published between 2015 and 2019, the original RCTs ranged from 7-49, with sample sizes ranging from 336-1989. The quantitative meta-analysis found that adjuvant CT of SFI improved the clinical response rate (RR=1.37, 95% CI=1.28, 1.46; P<0.00001) and the KPS score (RR=1.66, 95% CI 1.54, 1.79, P<0.00001) of patients with BC. In terms of immune function, CD3+ (SMD=1.51, 95% CI 0.91, 2.10; P<0.00001), CD4+ (SMD=1.87, 95% CI 1.18, 2.56; P<0.00001), CD4+/CD8+ (SMD=0.86, 95% CI 0.48, 1.23; P<0.00001), and NK cell levels (SMD=0.94, 95% CI 0.63, 1.24; P<0.00001) in the adjuvant CT group SFI were better than those with CT alone. Adverse reactions following SFI adjuvant CT showed reduced incidence of leukopenia (RR=0.53, 95% CI 0.46, 0.62; P<0.00001) and gastrointestinal reactions (RR=0.48, 95% CI 0.39, 0.58; P<0.00001). However, the GRADE results showed 'very low' to 'moderate' evidence for the 42 outcomes, without high-quality evidence supporting them, limited mainly by deficiencies in the design of RCTs (42/42, 100.00%), inconsistency (19/42, 45.24%), publication bias (41/42, 97.62%), and inaccuracy (3/42, 7.14%). The unsatisfactory results of AMSTAR-2, PRISMA 2020, and ROBIS were limited to lack of registration of study protocols, explanation of inclusion basis of RCTs, description of funding sources for the included studies, incomplete search strategy and screening process, addressing heterogeneity and sensitivity, and reporting potential conflicts of interest. Conclusion Adjuvant CT with SFI for BC had better benefits and a lower risk of adverse events. The methodology and quality of the evidence are generally low, highlighting a need of greater attention during study implementation. More objective and high-quality studies are needed to verify the efficacy of adjuvant CT with SFI in clinical decision-making for BC.